Local anaesthetic infiltration in rubber band ligation of rectal haemorrhoids: study protocol for a three-arm, double-blind randomised controlled trial (PLATIPUS trial). Issue 3 (8th March 2023) - Watson, Eleanor G R; Qin, Kirby R; Smart, Philip J; Burgess, Adele N; Mohan, Helen M; Proud, David M
Abstract : Introduction: Rubber band ligation ('banding') is a common approach for the management of symptomatic haemorrhoids. However, up to 90% of patients experience postprocedural pain, and there is no consensus regarding the optimal analgesic strategy. In practice, patients may receive submucosal local anaesthetic, pudendal nerve block or routine periprocedural analgesia. The aim of this study is to compare the efficacy of submucosal local anaesthetic, pudendal nerve block and routine analgesia for postprocedural pain in patients undergoing haemorrhoid banding. Methods and analysis: This is a multicentre, prospective, three-arm, double-blind randomised controlled trial of adults booked for haemorrhoid banding. Participants will be randomised to one of three groups in a 1:1:1 ratio: (1)submucosal bupivacaine injection; (2) pudendal nerve ropivacaine injection and (3) no local anaesthetic. The primary outcome is patient reported postprocedural pain (scored 0–10) from 30 min to 2 weeks. Secondary outcomes include postprocedural analgesia use, time to discharge, patient satisfaction, time to return to work and complications. A sample size of 120 patients is required to achieve statistical significance. Ethics and dissemination: This study received Human Research Ethics Approval from the Austin Health Human Research Ethics Committee (March 2022). Trial results will be submitted to a peer-reviewed journal, and presented at academic meetings. A summary of the trial results will be made available to study participants on request. Trial registration number: ACTRN12622000006741p.